Implementation of loss adjustment process at Crawford & Company Adjusters (M) Sdn Bhd / Azizul Huzaini Sejani - Sejani, Azizul Huzaini (Faculty of Business and Management, 2010)
This research conducted focusing on “The Effectiveness of Integrated Marketing Communication Used by UMW Pennzoil Distribution Sdn Bhd, Shah Alam in Promoting Lubricant Oil”. Since a marketing communication is quite important nowadays, customers’ point of view are very important to ensure the effectiveness of marketing communication in term of marketing activities is high. The main objectives are (1) To investigate whether UMW Pennzoil Sdn Bhd is able to create an effective communication using their integrated marketing communication tools, (2) To determine the level of commitments for promotions by UMW Pennzoil Sdn Bhd, (3) To determine the most effective element in Integrated Marketing Communication for promoting lubricant oil and (4) To determine the solution and recommendation for suitable marketing communication tools. The respondents of this study were public in Shah Alam, Selangor area. 100 questionnaires had been distributed among them. The researcher had used convenience sampling as the sampling technique. The process of analyzing and interpreting data has been presented by tables and figures using method of analysis such as reliability analysis, frequency analysis, descriptive analysis and correlation analysis. The recommendations are the company have to enhance more on their marketing activities such as advertising, public relation and sales promotion in order to increase their sales of their Lubricant Oil.